2012
DOI: 10.1016/j.jcin.2012.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Evaluation of Edwards SAPIEN Positioning During Transcatheter Aortic Valve Implantation With Correlates for Device Movement During Final Deployment

Abstract: The final Edwards SAPIEN position is mostly aortic in relation to the lower sinus border. There is an operator-independent upward movement of the device center during the final stage of implantation. Anticipated upward movement of the device should influence its positioning before final deployment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…Fluoroscopy has shown that the device-center upper movement during final deployment was (on average) 2.0 ± 1.43 mm (range -1.3 to 4.6 mm), with shortening of the device due to asymmetrical upward movement of the ventricular edge of THV by 3.2 ± 1.4 mm and the upper (aortic) edge by only 0.75 ± 1.50 mm (67). The optimal final THV deployment position resulted in 17% of the THV below the base of the aortic sinuses (determined by pigtail catheter position or aortography); this translated to 33% of the valve below the sinuses during the final pacing run.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluoroscopy has shown that the device-center upper movement during final deployment was (on average) 2.0 ± 1.43 mm (range -1.3 to 4.6 mm), with shortening of the device due to asymmetrical upward movement of the ventricular edge of THV by 3.2 ± 1.4 mm and the upper (aortic) edge by only 0.75 ± 1.50 mm (67). The optimal final THV deployment position resulted in 17% of the THV below the base of the aortic sinuses (determined by pigtail catheter position or aortography); this translated to 33% of the valve below the sinuses during the final pacing run.…”
Section: Complicationsmentioning
confidence: 99%
“…Although operator-independent motion of the balloon-expandable valve is usually predictable and has been well described for the first generation and second generation balloon-expandable valves (67), there is rarely an unexpected extreme motion of the valve. Embolization of the valve into the aorta may itself result in aortic trauma, but if not, intentional repositioning of the valve into the descending aorta beyond the great arteries (Figure 34) may be necessary before attempted deployment of a second valve at the aortic annulus.…”
Section: Complicationsmentioning
confidence: 99%
“…Considerably high implantation may result in paravalvular regurgitation, coronary flow obstruction and device embolisation into the thoracic aorta [10, 60]. …”
Section: Post-implantation Imagingmentioning
confidence: 99%
“…Unlike SAVR in which the valve is directly sutured to the aortic annulus, in TAVR the valve is ‘anchored’ only by contact and friction forces between the native root and the deployed stent. Because the deployment position is based on angiographic imaging and is performed during heart pacing, a possible suboptimal location can cause longitudinal shift of the prosthesis during the balloon inflation (10), and thus lead to procedural failure. The deployed valve may be susceptible to migration, where the prosthetic valve dislocates toward either the LV cavity (11) or the aorta (12).…”
Section: Introductionmentioning
confidence: 99%